Post-Pandemic Vulnerabilities and Policy Directions in Indonesia's Pharmaceutical Supply Chain - Arum Purwaning Asih (Journal of Research in Social Science and Humanities, 2025)
The COVID-19 pandemic has revealed significant vulnerabilities in Indonesia's pharmaceutical supply chain, especially due to the very high dependence on imports of Active Pharmaceutical Ingredients (API), which reaches more than 90% of the national demand. This dependency poses risks such as distribution delays, price fluctuations, and protectionist policies from exporting countries. This condition is urgent and needs improvement to prevent disruption to the national pharmaceutical supply chain in the future. This study analyzes Indonesia's pharmaceutical supply chain post-pandemic, identify the keyrisks faced, and evaluate the role of government policies in strengthening national pharmaceutical resilience. Using a literature review method, this study examines findings from relevant journals, government reports and policy documents in the past five years. The results show that import dependency creates major risks, including distribution delays, raw material price fluctuations, and the impact of exporting countries' protectionist policies. Although the government has initiated strategic policies such as change source and domestic component level policy, their implementation still faces obstacles, such as limited local production capacity and complex regulations. Therefore, a holistic approach is needed that includes diversifying raw material sources, investing in local technology, and strengthening logistics infrastructure. In conclusion, this strategic step is not only important to reduce import dependency, but also to ensure Indonesia's future pharmaceutical resilience.